#TITLE_ALTERNATIVE# - SUDJATMIKO (NIM : 12211055), MOHAMMAD
MEOR (Microbial Enhanced Oil Recovery) is a method for increasing oil recovery using chemical compounds that produced by microbes. Various type of microbes have been investigated of their ability to increase oil recovery in laboratory. Further efforts are necessary to forecast and evaluate the performance of wells that can be done in the scale field development planning, but until now there has been not provided a method of performance evaluation of microbes injection wells to determine well production prediction based productivity index. The method used is to generate a simulation model injection technique huff and puff wells using reservoir simulators blackoil. Model simulations were carried out in order to approach the process engineering MEOR on the real field. Model validation represent the conditions on the field. Method validation is done by well tesing. The model should represent the condition of the field if it has a parameter value equal or well testing results in accordance with the model input parameters. The input parameters in the model is divided into two input parameters of Microbial and input parameters and reservoir fluid. Microbes for input parameters can be used on the results of laboratory studies conducted by previous researchers. Results forecasting performance of model with process MEOR compared to the initial model is when a natural depletion wells basecase. After that, we do sensitivity analysis of the parameters that affect the performance comparison results shown by the ratio of the well productivity index. Subsequently generate a correlation based on data from the results of numerical simulations carried out on the results of sensitivity analyzes. The results of model simulations show that the process MEOR with microbial C were able to decrease the viscosity of 40% provides an increase in oil production of 1.8 bbl / day of basecase conditions and for a period of one year increase in cumulative production of oil amounted to 796.35 bbl of basecase conditions. The results of the sensitivity analysis, there are six parameters that are used to generate the corelation. There are biosurfactant concentration, surface tension, porosity, permeability, oil viscosity and oil saturation. Corelation performed on data obtained with an error rate of 2.9%. Correlations have been made can be used to evaluate and design the stimulation wells microbial huff and puff.